LEARNING MODEL TO IMPROVE THE ABILITY TO UNDERSTAND MATHEMATICAL CONCEPTS - Syamsul Huda; Lusi Anggraini; Rizka Dwi Saputri; Muhamad Syazali; Rofiqul Umam (Universitas Suryakancana, 2019)
Teaching and learning process to determine student learning outcomes requires the selection of appropriate learning models so that it can provide maximum learning impact. This study aims to determine the effectiveness of better learning models for the ability to understand mathematical concepts. This type of research is quantitative using the Quasi-experimental design method. Data collection in this study uses a description test with the type of questions based on indicators of mathematical concept understanding ability. Hypothesis testing uses a non-correlated 2-sample t test with decisions taken through the left-side test. This shows that the Flipped Classroom learning model is more effective than the Auditory Intellectually Repetition learning model in influencing students' mathematical concepts